(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In the given article it is considered ecology problems caused in the result of irresponsible approach of a man to the environment. Destroying activity of a contemporary man, which have been lasting for years, toward to the nature led to scaled ecology catastrophes. The only solution of this problem is formation and upbringing of coming generation according to required ecology behavior. In order to realize put aims it is necessary to elaborate and improve of continuous ecology education and upbringing. In the article it was reviewed ways of continuous ecology upbringing and education which will be later base for formation of ecology culture of an individual. Aiming to identify ecology level of individual there was conducted sociological research. Along with it there was analyzed activity of the main institutions of ecology culture and identiﬁ ed the role of social institutions (family, education, mass media means) in formation of ecology culture. Keywords: ecological upbringing, ecology education, ecology of a culture, social institutions, an individual.